2013
DOI: 10.1534/genetics.113.153981
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Control of Epigenetic Processes in Yeast and Human Cells

Abstract: The vitamin folate is required for methionine homeostasis in all organisms. In addition to its role in protein synthesis, methionine is the precursor to S-adenosyl-methionine (SAM), which is used in myriad cellular methylation reactions, including all histone methylation reactions. Here, we demonstrate that folate and methionine deficiency led to reduced methylation of lysine 4 of histone H3 (H3K4) in Saccharomyces cerevisiae. The effect of nutritional deficiency on H3K79 methylation was less pronounced, but w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 79 publications
0
51
0
Order By: Relevance
“…28,29 Here, we show that SET1 expression and SET1 binding on the endothelin-1 promoter can be upregulated in cultured endothelial cells and in the lungs in mice. More importantly, augmented expression and activity of SET1 by Ang II parallel the accumulation of H3K4Me3 on the endothelin-1 promoter and consequently endothelin-1 transactivation.…”
Section: Discussionmentioning
confidence: 73%
“…28,29 Here, we show that SET1 expression and SET1 binding on the endothelin-1 promoter can be upregulated in cultured endothelial cells and in the lungs in mice. More importantly, augmented expression and activity of SET1 by Ang II parallel the accumulation of H3K4Me3 on the endothelin-1 promoter and consequently endothelin-1 transactivation.…”
Section: Discussionmentioning
confidence: 73%
“…In Saccharomyces cerevisiae, folate and methionine deficiency leads to reduced H3K4me2 and H3K4me3 levels (Sadhu et al 2013). Knockout of the enzymes sam1 or sam2, which are the orthologs of MAT, also diminishes H3K4me3 levels .…”
Section: Chromatin Methylation Is Modulated By Nutrient Availabilitymentioning
confidence: 99%
“…During methylation, SAM donates its methyl group and is converted to S-adenosylhomocysteine (SAH). SAH is then hydrolyzed to homocysteine, which is converted back to methionine in a reaction that requires folate and cobalamin (i.e., vitamin B12) [41]. Consequently, histone methylation status might be influenced by fluctuations in SAM or regulators of SAM synthesis.…”
Section: Dynamic Histone Methylation and Demethylationmentioning
confidence: 99%
“…The idea that folate is used to regenerate methionine (hence, SAM), and sustain methylation, was recently tested in yeast [41]. Controls showed that H3K4 methylation in folate-synthesis-deficient yeast cells was rescued by exogenous folate; similarly, exogenous methionine rescued H3K4 methylation in methionine-synthesis-deficient yeast.…”
Section: Dynamic Histone Methylation and Demethylationmentioning
confidence: 99%
See 1 more Smart Citation